Comparative analysis of cecal microbiota and metabolites in relation to growth performance of Tibetan and Hu sheep - Yang, Feifei; Yang, Lei; Shi, Jinping; Tang, Zhixiong; Meng, Quanlu; Pi, Zhengwu; Li, Haoke; Liu, Ting; Zhang, Changji; Cheng, Shuru (Frontiers in Microbiology, 2026)
The gastrointestinal microbiota play a crucial role in the growth and development of sheep. However, most existing studies have focused on the rumen microbiota, while comparatively little attention has been given to the cecum—the primary site of hindgut fermentation—and its metabolic functions. To investigate the potential influence of cecal microbiota and their metabolites on growth performance, we selected healthy male lambs of Tibetan and Hu sheep breeds at 3 months of age with similar body weights (19.55 ± 1.51 kg). After 3 months of feeding under identical conditions, the lambs were slaughtered, and cecal contents were analyzed using 16S rRNA gene sequencing and liquid chromatography–mass spectrometry (LC–MS). Results showed that Hu sheep exhibited significantly superior growth performance [body weight, average daily gain (ADG), and body size] compared to Tibetan sheep, accompanied by higher cecal concentrations of acetic, propionic, and butyric acids (p < 0.05). Microbial diversity analysis revealed that Firmicutes and Bacteroidetes were the dominant microbial phyla in the cecum of both breeds. At the genus level, the relative abundances of norank_f__Lachnospiraceae, UCG-005, and norank_f__Eubacterium_coprostanoligenes_group were higher in Tibetan sheep, whereas Rikenellaceae_RC9_gut_group and Bacteroides predominated in Hu sheep. Metabolomic profiling identified 986 differentially abundant metabolites, primarily enriched in nucleotide, tryptophan, and arachidonic acid metabolism pathways. Notably, five bacterial genera (norank_f__Christensenellaceae, Negativibacillus, Christensenellaceae_R-7_group, norank_o__Clostridia_UCG-014, and Prevotellaceae_NK3B31_group) and five key metabolites (4-O-(indole-3-acetyl)-D-glucopyranose, 5Alpha-cyprinol, 2-Hydroxyphenylacetic acid, Myrianthic acid, and Indole-3-carboxylic acid-O-sulfate) were identified as closely associated with growth traits. Correlation analyses among microorganisms, metabolites, and growth performance revealed significant positive associations between these bacterial genera, metabolites, and growth traits. Collectively, these findings suggest that specific gut microbes and metabolites synergistically enhance host growth and development by modulating energy metabolism pathways. This study provides novel insights into the cooperative mechanisms through which gut microbiota and metabolites regulate growth performance in sheep.